The Historical Dynamics of Islamic Civilization in the Formation of Political Institutions, Power, and the Development of the Islamic World Civilization - Ahsan Hakim; Heri Rifhan Halili; Febry Suprapto; Babussalam (PT. Education Research Center, 2025)
This study aims to analyze the historical dynamics of Islamic civilization in the formation of political institutions, the construction of power, and the development of the broader Islamic world. It is motivated by the academic need to understand Islamic politics not merely as a normative system or as a debate over state forms, but as a historical process that continuously changed in response to the social, cultural, economic, and geopolitical contexts of Muslim societies. This research employs a qualitative approach through library research. The data were obtained from primary and secondary sources related to Islamic civilization, Islamic political thought, the caliphate, imamate, sultanate, political legitimacy, bureaucracy, and the role of political institutions in advancing Islamic knowledge and culture. The data were analyzed using a historical-conceptual approach involving data condensation, thematic categorization, interpretation, and conceptual synthesis. The findings show that Islamic political institutions developed through four major patterns: normative-prophetic, institutional-administrative, dynastic-territorial, and civilizational-pluralistic. These patterns demonstrate that power in Islamic history was not based solely on religious legitimacy, but also on the ability to build political stability, administrative structures, legal systems, economic networks, military organization, and socio-intellectual relations. The study concludes that Islamic civilization was formed through a dialectical relationship between values, institutions, power, and civilizational production. Its main contribution lies in proposing a historical-institutional framework for understanding Islamic political history in a more critical, integrative, and contextual way.